Prove $lim_{nmapsto 0}[(psi(n)+gamma)psi^{(1)}(n)-frac12psi^{(2)}(n)]=2zeta(3)$

How to prove that
$$lim_{nmapsto 0}[(psi(n)+gamma)psi^{(1)}(n)-frac12psi^{(2)}(n)]=2zeta(3) ?$$

I encountered this limit while I was trying to solve $int_0^1frac{ln xln(1-x)}{x(1-x)}dx$ using the derivative of beta function but I have no idea how to tackle this limit.

We know that this integral is very simple :

$$int_0^1frac{ln xln(1-x)}{x(1-x)}dx=int_0^1frac{ln xln(1-x)}{x}dx+underbrace{int_0^1frac{ln xln(1-x)}{1-x}dx}_{1-xto x}$$

$$=2int_0^1frac{ln xln(1-x)}{x}dx=2zeta(3)$$

but using integration does not always work for high-power log integrals and beta function would be the right tool but my problem is only when $nto 0$. Any help would be appreciated.

Note: No solutions using asymptotic expansion please.

Mathematics Asked on November 18, 2021

2 Answers

2 Answers

We shall be using the following reflection formulas to evalute the limit.

$$psi_0(1-x)-psi(x)=frac{pi}{tan pi x}\ psi_1(1-x)+psi_1(x)=frac{pi^2}{sin^2 pi x}\psi_2(1-x)-psi_2(x)=frac{d^2}{dx^2}(picotpi x)=frac{2pi^3cotpi x}{sin^2pi x}$$

These give us $$lim_{xto 0}left[left(psi(1-x)+gamma -frac{pi}{tan pi x}right)left(frac{pi^2}{sin^2pi x}-psi_1(1-x)right)-frac{1}{2}left(psi_2(1-x)-frac{2pi^3cotpi x}{sin^2pi x}right)right]$$ Making the use of $displaystyle lim_{xto 0} x^{-1}sin x =1=lim_{xto 0}x^{-1} tan x$ the last expression can be reduced to $$lim_{xto 0}left[left(psi(1-x)+gamma -frac{1}{ x}right)left(frac{1}{ x^2}-psi_1(1-x)right)-frac{1}{2}left(psi_2(1-x)-frac{2}{x^3}right)right] \=-frac{1}{2}psi_2(1-x)+lim_{xto 0} left(frac{psi(1-x)+gamma +xpsi_1(1-x)}{x^2}right)$$ since the latter limit obtained attains $0/0$ form so we evaluate it by L-hopital's rule $$-frac{1}{2}psi_2(1-x)+lim_{xto 0}frac{-psi_1(1-x)+0+psi_1(1-x)-xpsi_2(1-x)}{2x}=lim_{xto 0}left(-frac{1}{2}psi_2(1-x)-frac{1}{2}psi_2(1-x)right)=-psi_2(1)= -(-1)^{3} 2!zeta(3,1)=2zeta(3)$$

Answered by Naren on November 18, 2021

Solution due to my friend Khalef Ruhemi ( he is not a MSE user ):

Let $f(x)=(psi(x)+gamma)psi^{(1)}(x)-frac12psi^{(2)}(x)$



$$Longrightarrow psi^{(1)}(x)=psi^{(1)}(x+1)+frac1{x^2}$$

$$Longrightarrow psi^{(2)}(x)=psi^{(2)}(x+1)-frac{2}{x^3}$$

we have



$$lim_{xto 0}f(x)=$$ $$underbrace{lim_{xto 0}(gamma+psi(x+1))psi^{(1)}(x+1)}_{0 text{as $psi(1)=-gamma$}}+underbrace{lim_{xto 0}frac{gamma+psi(x+1)-frac12x^2psi^{(2)}(x+1)-xpsi^{(1)}(x+1)}{x^2}}_{text{L'Hopital}}$$

$$=lim_{xto 0}frac{psi^{(1)}(x+1)-xpsi^{(2)}(x+1)-frac12 x^2psi^{(3)}(x+1)-psi^{(1)}(x+1)-xpsi^{(2)}(x+1)}{2x}$$

$$=lim_{xto 0}(-psi^{(2)}(x+1)-frac14 xpsi^{(3)}(x+1))=-psi^{(2)}(1)=2zeta(3)$$

Answered by Ali Shadhar on November 18, 2021

Add your own answers!

Related Questions

Retract of $F_2$ onto $[F_2,F_2]$

2  Asked on January 8, 2021 by sasha


Finding the order of a pole of a complex function

1  Asked on January 7, 2021 by prasiortle


How To Prove This Is Continuous Or Discontinuous

1  Asked on January 7, 2021 by mat-rhine


Inverse of a 3×3 block matrix

1  Asked on January 7, 2021 by dadoo


Ask a Question

Get help from others!

© 2021 All rights reserved.